Sifat-Sifat Konkrit Berkekuatan Tinggi Yang Mengandungi Abu Sekam Padi - Ridzuan Ramli, Hannan (Universiti Sains Malaysia, 2006)
High Strength Concrete (HSC) mixes were produced using Rice Husk Ash (RHA) as a partial cement replacement material at replacement levels from 5%, 10%, 15% and 20%. The effects of RHA addition on workability, compressive strength and strength development of HSC have been studied. RHA has about 95% silica content. It was produced by burning (calcinations) rice husk at temperature of 600 °C for 4 hours. A total of 150 test specimens were prepared and tested at the ages of 1, 3 7, 28, 56 and 84 days. In order to study the effects of RHA inclusion, Slump, Flow Table, Compressive Strength, Permeability, Porosity and Ultrasonic Pulse Velocity tests have been performed. Test results indicate that the inclusion of RHA tends to reduce the flow, although the slump values were not affected. Early age compressive strength was reduced, but long term strength was increased. The concrete containing 10% RHA exhibited the highest 84 days strength. In addition, the porosity and permeability of concrete containing RHA is lower than the control from the age of 3 to 84 days. The effect of RHA seems to increase the UPV of concrete compared to the control. Therefore, the RHA produced could be potentially used as a mineral admixture, to improve the properties and performance of concrete.